Steady State Thermo XFEM Fracture Analysis of Isotropic and an Isotropic FG Plate with Inclined Center Crack - Khalaf, Hassanein Ibraheem; Mehbes, Haider Khazal; Nassar, Ameen Ahmed (Basrah Journal for Engineering Sciences, 2018)
The extended-finite element method (X-FEM) is used for crack analysis of orthotropic and isotropic functionally- graded composite material (FGCM) plate with slanted crack under thermal loadings. The enrichments functions of discontinuity are implemented. Mixed-mode SIFs are calculated in isotropic and orthotropic FGMs. Gaussian technique (Q4) has been applied in numerical calculation of interaction of solution. Thermal effects, fundamental equations, the interaction integral of non-homogeneous cases (M-integral), and proposal numerical integration rule are set to simulate and to debate the accuracy of the present work results in comparing with the results of the references that available in the literature. In addition, the effect of size of crack is studied to discuss the values of energy release rate and stress intensity factors with different crack angles. The present study is implemented by using MATLAB program to present steady state thermo XFEM fracture analysis of isotropic and an isotropic FG plate with inclined center crack.